Antidepressant use and risk of hip fractures among community‐dwelling persons with and without Alzheimer's disease. (5th January 2017) - Torvinen‐Kiiskinen, Sanna; Tolppanen, Anna‐Maija; Koponen, Marjaana; Tanskanen, Antti; Tiihonen, Jari; Hartikainen, Sirpa; Taipale, Heidi
Abstract : Objective: To study whether antidepressant use is associated with an increased risk of hip fracture among community‐dwelling persons with and without Alzheimer's disease (AD), and to compare the risk according to duration of use and between antidepressant groups. Methods: Retrospective cohort study, including 50, 491 persons with AD (mean age 80) and 100, 982 comparison persons without AD from Finnish register‐based MEDALZ cohort. Antidepressant use was compared with nonuse with Cox proportional hazard models. Incident users were identified with a one year washout period from Prescription register data. Main outcome was hospitalization due to hip fracture. Results: During antidepressant use, the age‐adjusted rate of hip fractures per 100 person‐years was 3.01 (95% CI 2.75–3.34) among persons with and 2.28 (1.94–2.61) among persons without AD. Antidepressant use was associated with an increased risk of hip fracture among persons with and without AD (adjusted HR 1.61, 95% CI 1.45–1.80 and 2.71, 2.35–3.14, respectively) compared with nonuse. The risk was most prominent in the beginning of use and was elevated even up to 4 years. The risk was increased with all of the most frequently used antidepressants. Conclusion: Antidepressant use is associated with an increased risk of hip fracture among older persons. Copyright © 2017 John Wiley & Sons, Ltd.